Neural Regeneration: Role of Traditional Chinese Medicine in Neurological Diseases Treatment - Zhi-Li Ren; Ping-Ping Zuo (Elsevier, 2012)
The effects of a single compound and a mixture of traditional Chinese medicine (TCM) on promoting proliferation, differentiation, and migration of neural stem cells and regulating their microenvironment have been observed by Chinese scholars in recent years. These results showed good prospects in improving neural regeneration and repair of neurological disorders such as ischemic brain injury, Alzheimer's disease, Parkinson's disease, and depression. According to the TCM theory, the relationship between life of an individual and the disease was regarded as an entirety, and the theory emphasized the treatment based on syndrome differentiation since ancient times. In this paper, we attempted to introduce these medicines, which belong to natural products and have already been proved to possess clear therapeutic action on human bodies in the clinical setting. We summarized their effects promoting brain neurogenesis and repairing brain injuries in animal models and some mechanisms at the cellular and molecular levels. Keywords:: traditional Chinese medicine (TCM), neural stem cell, neural regeneration, neurological disease